2019
DOI: 10.1111/ijfs.14315
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the survival kinetics of Salmonella spp. on the surface of ripened raw milk cheese during storage at different temperatures

Abstract: The aim of this study was to determine the survival kinetics of Salmonella enterica subsp. enterica in ripened raw milk cheese. Cheese samples inoculated with S. enterica subsp. enterica were stored at 5, 15 and 25°C and analysed in terms of physico-chemical and microbiological characteristics. Three primary models were used to estimate the kinetic parameters of S. enterica subsp. enterica. The secondary Arrhenius model was used to establish the relationship between temperature and parameter a of the Weibull m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Among the environmental conditions affecting microbial behavior during storage, temperature is the most widely investigated [ 74 , 75 ]. It has been demonstrated that when the physicochemical characteristics of cheeses allow pathogen growth, growth rates are higher at higher storage temperatures [ 8 , 24 , 76 ].…”
Section: Main Factors Governing Microbial Fate In Cheesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the environmental conditions affecting microbial behavior during storage, temperature is the most widely investigated [ 74 , 75 ]. It has been demonstrated that when the physicochemical characteristics of cheeses allow pathogen growth, growth rates are higher at higher storage temperatures [ 8 , 24 , 76 ].…”
Section: Main Factors Governing Microbial Fate In Cheesesmentioning
confidence: 99%
“…At first, a fraction of the population is rapidly inactivated and afterwards a slowing down in inactivation, which is known as the tailing effect, is noted. These non-linear survival behaviors have been described by the Geeraerd [ 79 ], Gompertz [ 81 ], and Weibull [ 75 , 80 , 82 , 84 , 109 ] primary models. The shoulder effect describes the existence of a lag period prior to inactivation representing the initial resistance of microorganisms.…”
Section: Models Of Microbial Behavior During Cheese Production Andmentioning
confidence: 99%
See 1 more Smart Citation
“…The TEMPO ® system relies upon the detection of the number and volume of positive wells (fluorescent or non-fluorescent) and statistical methods that are based on the most probable number (MPN) approach to perform bacterial enumeration [28,29]. The TEMPO ® system is increasingly used in the food industry, which takes advantage of its semi-automated process, built-in sample scanner for traceability purposes and its speed in achieving bacteriological count and identification without additional identification tests [30,31]. Human milk and dairy products have similar matrices in terms of fat and inhibitory substances, which www.videleaf.com suggest that the TEMPO ® system might be an asset for milk banks.…”
Section: Introductionmentioning
confidence: 99%
“…The TEMPO® system relies upon the detection of the number and volume of positive wells (fluorescent or non-fluorescent) and statistical methods that are based on the most probable number (MPN) approach to perform bacterial enumeration ( 28 , 29 ). The TEMPO® system is increasingly used in the food industry, which takes advantage of its semi-automated process, built-in sample scanner for traceability purposes and its speed in achieving bacteriological count and identification without additional identification tests ( 30 , 31 ). Human milk and dairy products have similar matrices in terms of fat and inhibitory substances, which suggest that the TEMPO® system might be an asset for milk banks.…”
Section: Introductionmentioning
confidence: 99%